Dislocation mechanisms in a zirconium alloy in the high-temperature regime: An in situ TEM investigation. (1st April 2015) - Caillard, Daniel; Rautenberg, Martin; Feaugas, Xavier
Abstract: Dislocation mechanisms responsible for the high-temperature mechanical properties of a Zr alloy have been investigated using in situ straining experiments between 250 °C and 450 °C. At 250 °C and 300 °C, the results show a steady and homogeneous dislocation motion in prismatic planes, with little cross-slip in the pyramidal and/or basal planes. At 350 °C, the kinetics of mobile dislocations becomes very jerky and inhomogeneous, in agreement with a dynamic strain aging mechanism. Above this temperature, the motion is again steady and homogeneous. Extensive cross-slip forms super-jogs which are efficient pinning points against the glide motion. These super-jogs move by glide along the Burgers vector direction, never by climb. The glide velocity between super-jogs is linear as a function of the total driving stress (applied stress minus line-tension stress due to dislocation curvature), in agreement with the solute dragging mechanism. The origin of the stress–strain rate dependence with an exponent larger than unity is then discussed.